Imaging Glycans in Zebrafish Embryos by Metabolic Labeling and Bioorthogonal Click Chemistry - Jiang, Hao (MyJove Corporation, 2011)
Imaging glycans in vivo has recently been enabled using a bioorthogonal chemical reporter strategy by treating cells or organisms with azide- or alkyne-tagged monosaccharides(1, 2). The modified monosaccharides, processed by the glycan biosynthetic machinery, are incorporated into cell surface glycoconjugates. The bioorthogonal azide or alkyne tags then allow covalent conjugation with fluorescent probes for visualization, or with affinity probes for enrichment and glycoproteomic analysis. This protocol describes the procedures typically used for noninvasive imaging of fucosylated glycans in zebrafish embryos, including: 1) microinjection of one-cell stage embryos with GDP-5-alkynylfucose (GDP-FucAl), 2) labeling fucosylated glycans in the enveloping layer of zebrafish embryos with azide-conjugated fluorophores via biocompatible Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC), and 3) imaging by confocal microscopy(3). The method described here can be readily extended to visualize other classes of glycans, e.g. glycans containing sialic acid(4) and N-acetylgalactosamine(5, 6), in developing zebrafish and in other living organisms.